Prenatal Diagnosis and Pathology of Laryngeal Atresia in Congenital High Airway Obstruction Syndrome - Piya Chaemsaithong; Tharintorn Chansoon; Boonsri Chanrachakul; Suchin Worawichawong; Sansanee Wongwaisayawan; Patama Promsonthi (Case Reports in Radiology)
Congenital high airway obstruction syndrome is a rare but life-threatening condition. Therefore, prenatal diagnosis is important. The obstruction can be due to laryngeal/tracheal atresia or external compression. While a differential diagnosis with congenital cystic adenomatoid malformation (CCAM) type III may be difficult, it is still possible with ultrasonography. In this study, we report a case of bilateral echogenic lungs with hydrops fetalis. After the prenatal diagnosis of laryngeal atresia, the couple opted to have an elective termination of pregnancy performed at 20 weeks of gestation. The diagnosis was confirmed by a complete pathological examination.